Soils and Land Capability Classes of the Kosi Region, Bihar - Das, K.N. (Journal of Soil and Water Conservation, 2022)
The composition of the soil in a depositional area such as of the Kosi is largely determined by the river system but its character changes from one part to another, depending on the nature of sand, silt and clay deposited by streams of the Kosi system, Burhi Gandak, Baghmati and Karnla-Balan etc. The Kosi river, in particular, has converted the fertile lands into a wilderness of pure sand and infertile waste. The coarse-grained sandy soils deposited by the river in the northern and central parts of Purnea and Saharsa have rendered good soils almost infertile. The cultivation in some patches in areas having vast stretches of waste land has become uneconomic.